Fertility Effects of Child Benefits - Regina T. Riphahn; Frederik Wiynck (Institute of Labor Economics (IZA), 2017)
We exploit the 1996 reform of the German child benefit program to identify the causal effect of heterogeneous child benefits on fertility. While generally the reform increased child benefits, the exact amount of the increase varied by household income and the number of children. We use these heterogeneities to identify their causal effects on fertility in a difference-in-differences setting. We apply the large samples of the German Mikrozensus and the rich data of the German Socio-economic Panel (SOEP). The reform effects on low income couples are not statistically significant. We find some support for positive fertility effects for higher as opposed to lower income couples deciding on a second birth.
Keywords: J13; I38; C54; 330; child benefits; fertility; tax allowance; causal effect; difference-in-differences; Mikrozensus; SOEP